Impact of macronutrients printability and 3D-printer parameters on 3D-food printing: A review - Pérez, Bianca; Nykvist, Hanna; Brøgger, Anja F.; Larsen, Maria Barmar; Falkeborg, Mia Fiilsøe (Food chemistry, 2019)
•Rheological properties and 3D-printer parameters can determine food printability.•Every food matrix needs to be optimized prior to being used for 3D-printing.•Studies regarding 3D-printing protein and lipids enriched matrix are needed. In recent years, 3D-printing has received high attention globally in personalized meal production and customized food design for its potential advantages over traditional processing. For a material to be printed it needs to be easily extruded from the nozzle of the printer and it needs to hold its structure after deposition. Additives such as thickening and gelling agents can be used for a food system to achieve suitable structure for printing. Various literature reports have demonstrated that rheological properties such as the storage modulus, yield stress, consistency index and flow behavior index can predict the printability of a material and 3D-printer parameters such as nozzle speed movement and layer height have an impact on the final quality of the printed structure. The present review provides a comprehensive overview of the impact of macronutrients printability and 3D-printer parameters on 3D-food printing, and offers new opportunities to bring 3D-food printing for personalized meal production closer to industry application.